Desempenho do cimento Portland branco com escória de alto-forno e ativador químico frente ao ataque por sulfato de sódio - Veiga, Karina Kozoroski (2011)
Sulfate ions found in seawater, groundwater and wastewater are aggressive agents that can result in severe concrete degradation. They react with cement hydration products and depending on the associated cations present (magnesium, calcium, potassium, sodium, ammonium), their concentrations and the conditions of the environment, this can result in the formation of ettringite, gypsum or thaumasite, decalcification of C-S-H, processes which may cause expansion, cracking and loss of mass and strength.When high sulfate resistance is required, national and international standards prescribe the use of cement with high concentrations of granulated blast furnace slag (GBFS). By substituting GBFS for cement, lower amounts of clinker are required. In addition, the pozzolanic activity of GBFS takes up the CH released by the hydration of silicates (C3S e C2S), which then is not available to react with sulfate ions to form gypsum, resulting in a more dense paste with lower penetrability. GBFS is one of the few mineral admixtures that can be added to white Portland cement (WPC), a material with widespread usage in civil construction, particularly in cases where concrete is used as a finished surface for architectural impact. The substitution of GBFS for WPC offers technical and environmental gains as well as economic advantages due to the higher cost of WPC. This study investigated the sulfate resistance of WPC with 0%, 50% and 70% GBFS as a substitution for cement. A mix with 50% GBFS that was chemically activated with Na2SO4 (4% b/w of binder) was also studied. The performance of the blended cements was monitored by exposing the prepared mortar specimens to a solution of Na2SO4 (5%) for 2 years according to ASTM C1012/04 and using TG/DTA, DRX and SEM/EDX analyses of the paste samples. For comparison, the same blends prepared with high early strength Portland cement (PC) were also used. The results showed the benefits of the use of GBFS in both types of cement, with higher concentrations of slag resulting in improved sulfate resistance. The use of chemical activation reduced expansion when compared with mixtures without activation. For long-term exposure, all WPC blends showed lower expansion than the corresponding blends with PC. Microstructural analysis identified ettringite and gypsum as the main degradation products of the sulfate attack.